ANALISIS ASPEK KEAMANAN DAN PERLINDUNGAN DATA TANDA TANGAN DIGITAL DPJP (DOKTER PENANGGUNG JAWAB PELAYANAN) DALAM REKAM MEDIS ELEKTRONIK DI UPT RSUD HAJI MAKASSAR - Dian Ekawaty Dian; Andi Yaumil Bay R. Thaifur Yaumil; Nuraisyah; Zulkifli Ambo Zulkifli (Journal of Hospital Administration and Management (JHAM), 2026)
Background, improving the security of electronic medical record data is an important concern for users and application developers. Digital signatures in electronic transactions have an important role in authenticating the identity of the signer, as well as ensuring the integrity and authencity of electronic information. Electronic transaction have risks regarding the security and protection of signature data on electronic documents, especially in electronic medical records. Electronic documents unlike paper are easily edited seamlessly without traces such as scribbles so there is a possibility of manipulation or engineering. The purpose of this study was to analyze the security and data protection aspects of DPJP digital signatures in electronic medical records at the Makassar Haji Hospital. The method used is descriptive with a phenomenological approach. Data collected through purposive sampling technique. Results and conclusions obtained the security and protection of DPJP digital signature data in electronic medical records at the Makassar Haji Hospital is safe to use but has not used a certified signature. It is recommended that the Makassar Haji Hospital immediately strive for certified digital signatures to ensure the legal force of electronic medical records at RSUD Haji Makassar.